Primary fisheries management: A minimum requirement for provision of sustainable human benefits in small-scale fisheries - Cochrane, Kevern L. (2011)
The social and economic importance of small-scale fisheries is frequently under-valued, and they are rarely effectively managed. There is now growing consensus on how these fisheries could be managed for sustainability and to minimize the risks of crossing undesirable thresholds. Using a concept developed in health care, these approaches have been referred to as primary fisheries management. By encouraging the use of best-available information in a precautionary way, the approaches will facilitate sustainable use and should therefore be encouraged, but they accept high scientific and implementation uncertainties as unavoidable because of limited management and enforcement resources and capacity. It is important to recognize that this limitation will result in social costs, because application of a precautionary approach in the face of high uncertainties will require forgoing potential sustainable benefits. Acceptance of primary fisheries management as a final and sufficient goal could therefore add a further constraint on the possibility of fishing communities escaping the poverty trap. Primary fisheries management should be seen as a first and minimum target for fisheries where there is currently no or inadequate management, but the longer-term goal should still be well informed and adaptive management that strives for optimal benefits, referred to here as tertiary management.